DESIGN AND BASELINE CHARACTERISTICS OF THE COCOA SUPPLEMENT AND MULTIVITAMIN OUTCOMES STUDY OF COGNITION. (11th November 2018) - Espeland, M; Baker, L; Gaussoin, S; Manson, J; Pleasants, D; Rapp, S; Sesso, H; Shumaker, S
Abstract: Identifying a safe, affordable, and well-tolerated intervention that prevents or delays cognitive decline in older adults is critically important. There is growing evidence from basic science and small randomized trials that cocoa flavanols may provide protection against cognitive decline. COSMOS-MIND is an ancillary study to the COcoa Supplement and Multivitamin Outcomes Study (COSMOS), a large randomized controlled trial with more than 21000 participants. COSMOS-MIND examines the potential cognition-protecting effects of 3 years of treatment with cocoa flavanol extract (600mg/d), with and without co-administration of a standard multivitamin, concurrently with the evaluation of cardiovascular disease and cancer endpoints in the parent COSMOS trial. COSMOS-MIND uses validated telephone interviews to test whether these supplements improve cognitive function (or slow its decline). Proxy interviews are conducted for participants scoring below cognitive thresholds to inform adjudication of the study's cognitive impairment outcomes, including mild cognitive impairment, Alzheimer's and other forms of dementia. COSMOS-MIND enrolled 2, 282 randomized participants (60% women), median [range] age 73 [65–94] years. Its composite primary outcome is based on scores from standardized telephone assessments of memory, executive function, and global cognitive function. We used percentile regression to portray its relationships with baseline age. The observed trajectories demonstrate that the battery is sensitive to age-related differences. Data from additional baseline measures of subjective memory problems, depression, and insomnia will be presented. COSMOS-MIND demonstrates that large simple trials with cognitive and dementia outcomes derived from telephone interviews are feasible, and may serve as a model for future clinical trials testing well-tolerated interventions.